Dendogram reconstruction of Glenea spp. in Sarawak using binary Operational Taxonomic Unit of morphological character - NGUMBANG, JUAT; Mohd Azlan, Jayasilan (Malaysian Nature Society, 2025)
The genus Glenea (Cerambycidae: Lamiinae) comprises a diverse group of longhorn beetles distributed across tropical regions, with significant ecological and economic implications. This study employs a phenetic approach using external morphological characteristics to reconstruct the phylogenetic relationships of 59 Glenea species in Sarawak. A total of 154 binary-coded morphological characters were analysed using R statistical software to generate a dendrogram illustrating species clustering based on shared traits. Results reveal six major clades with varied numbers of species, the largest comprising 23 taxa. The reconstructed dendrogram provides insights into evolutionary patterns, morphological homology, and potential ecological adaptations within the genus. The study underscores the importance of morphology-based phylogenetics in species classification, particularly in taxa with limited molecular data availability. Further ecological and biological investigations are recommended to enhance understanding of species divergence and functional morphology in Glenea populations.